Co-loaded carbon-based catalyst as well as preparation method and application thereof
By developing Co-supported carbon-based catalysts and combining them with persulfate, the problem of insufficient biochemical properties of the pellet solution was solved, and a high selective conversion of lignin, a component difficult to biochemical degradation in the pellet solution was achieved, which significantly improved the biochemical properties of the pellet solution.
Patent Information
- Application Number
- CN202411232212.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively improve the biochemical properties of the sterilization fluid, especially in the high selective conversion of the difficult biochemically degraded component lignin.
A Co-supported carbon-based catalyst was developed to prepare a catalyst with rich active sites by mixing cobalt chloride, dopamine and H2O2 hexahydrate and pyrolytic, washing, drying and grinding, and combined with persulfate to activate organic components in the sterilization liquid.
This catalyst can significantly improve the biochemicalability of the sterilization liquid, and the biochemicalability is increased by more than 37% within 90 minutes. By regulating the active sites and oxidized species of the catalyst, high selective conversion of difficult-to-biochemical degradation components in the sterilization liquid is achieved.
Smart Images

Figure CN119524851A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multifunctional water treatment and purification materials, and in particular to a Co-loaded carbon-based catalyst and a preparation method and application thereof. Background Art
[0002] Biogas slurry is a liquid product produced by biodegradation and anaerobic fermentation of organic waste under the conditions of water content, temperature and methane bacteria. It has the characteristics of complex pollution components, poor biodegradability and unknown potential risks. 254 The value is 5.5~7.8cm -1 , the concentration of refractory lignin is as high as 3000-5200 mg / L. The uncertainty of biodegradability and biosafety of biogas slurry is an important factor restricting the resource utilization of biogas slurry, which is related to the different molecular weight distribution and composition characteristics of dissolved organic matter in biogas slurry. Among the many methods for improving the biodegradability of wastewater, Fenton-like advanced oxidation has the advantages of green, high efficiency, environmental friendliness, and simple operation, which has attracted widespread attention. Fenton-like systems have been applied to improve the biodegradability of wastewater such as antibiotic-containing wastewater, biochemical tailwater, and landfill leachate. However, in addition to the humic acid commonly found in biochemical tailwater and landfill leachate, biogas slurry usually contains high concentrations of lignin, which has a reticular structure and contains a large number of aromatic rings, a large molecular weight, and good stability. Lignin usually needs to be converted into humic acid by chemical means or high temperature (170-195°C), so lignin has the characteristics of being more difficult to be biodegraded. In view of the above problems, it is necessary to carry out technical innovation of Fenton-like systems, including the design of catalyst active sites and the optimization of Fenton-like systems, so as to achieve efficient conversion of lignin and humic acid in biogas slurry and improve the biodegradability of biogas slurry. Therefore, it is particularly important to develop persulfate catalysts with high activity and specificity. At present, heterogeneous catalysts such as metal oxides and metal-loaded carbon materials have been studied in depth, and studies have been conducted on the construction of Fenton-like systems using carbon-based materials as catalysts to improve the biodegradability of refractory wastewater. However, the degree of oxidation of organic matter in Fenton-like systems is difficult to control, resulting in the mineralization of most organic matter and waste of resources. The composition of oxidized species can be changed by regulating the composition of the active sites of the catalyst, thereby changing the conversion path of organic components. However, there are difficulties in regulating the active sites and oxidized species, and it is challenging to develop highly selective Fenton-like technologies for complex water bodies such as biogas slurry. There is still a lack of methods for regulating the generation of oxidized species in Fenton-like systems and the selective conversion of refractory biodegradable components of biogas slurry by the active sites of carbon-based catalysts, which hinders the application of carbon-based Fenton-like systems in improving the biodegradability of refractory wastewater. Summary of the invention
[0003] The purpose of the present invention is to provide a Co-loaded carbon-based catalyst and a preparation method and application thereof, so as to solve the technical problem in the prior art that the biodegradability of biogas slurry is insufficient and it is difficult to carry out highly selective conversion of the difficult-to-biodegrade components in the biogas slurry.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a Co-supported carbon-based catalyst, comprising the following steps:
[0006] 1) Cobalt chloride hexahydrate, dopamine and H2O2 are mixed and reacted, and then dried to obtain Co@PDA;
[0007] 2) The Co@PDA obtained in step 1) is pyrolyzed, washed, dried and ground in sequence to obtain a Co-supported carbon-based catalyst.
[0008] Furthermore, in step 1), the usage ratio of cobalt chloride hexahydrate, dopamine and H2O2 is 3-200 mM: 180-250 mM: 0.8-1.5 mL.
[0009] Furthermore, in step 1), the temperature of the mixing reaction is 18-40° C., and the mixing reaction time is 8-12 h; the temperature of the drying is 130-200° C., and the drying time is 1-5 h.
[0010] Furthermore, in step 2), the pyrolysis temperature is 600-800° C., the pyrolysis time is 2-4 hours, and the pyrolysis heating rate is 8-13° C. / min.
[0011] Furthermore, in step 2), the drying temperature is 60 to 80° C., and the drying time is 10 to 15 hours;
[0012] The grinding particle size is passed through a 80-150 mesh sieve.
[0013] The invention provides a Co-loaded carbon-based catalyst prepared by the above preparation method.
[0014] The present invention also provides an application of a Co-loaded carbon-based catalyst in activating peroxymonosulfate to degrade organic components in biogas slurry. The Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate are sequentially mixed and reacted.
[0015] Furthermore, the usage ratio of the Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate is 0.2-1.0 g: 250-500 mL: 2.0-6.0 mM.
[0016] Furthermore, the chemical oxygen demand concentration of the biogas slurry is 600-1000 mg / L, and the pH value of the biogas slurry is 3.0-11.0.
[0017] Furthermore, the reaction temperature is 24-26° C., and the reaction time is 1-3 hours.
[0018] Beneficial effects of the present invention:
[0019] (1) The Co-loaded carbon-based catalyst obtained in the present invention has a large specific surface area and has abundant active sites such as Co, lattice oxygen, and graphite N.
[0020] (2) Different Co-loaded carbon-based catalysts prepared in the present invention can activate peroxymonosulfate to produce active oxidative species of different compositions (such as 1 O2, OH and SO4 ·- ).
[0021] (3) Co-loaded carbon-based catalyst activated peroxymonosulfate, which increased the biodegradability of biogas slurry by more than 37% in 90 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD patterns of the Co-supported carbon-based catalysts obtained in Examples 1 to 4;
[0023] Figure 2 The XPS graphs of the Co-supported carbon-based catalysts obtained in Examples 1 to 4;
[0024] Figure 3 Schematic diagram of the improvement ratio of biodegradability of biogas slurry by Co-supported carbon-based catalyst obtained in Examples 1 to 4;
[0025] Figure 4 This is the UV spectrum of the biogas slurry after PMS treatment with the Co-supported carbon-based catalyst activated obtained in Examples 1 to 4. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a Co-supported carbon-based catalyst, comprising the following steps:
[0027] 1) Cobalt chloride hexahydrate, dopamine and H2O2 are mixed and reacted, and then dried to obtain Co@PDA;
[0028] 2) The Co@PDA obtained in step 1) is pyrolyzed, washed, dried and ground in sequence to obtain a Co-supported carbon-based catalyst.
[0029] In the present invention, in step 1), the usage ratio of cobalt chloride hexahydrate, dopamine and H2O2 is 3-200mM:180-250mM:0.8-1.5mL, preferably 10-150mM:200-230mM:1-1.3mL, further preferably 30-100mM:220mM:1.2mL, and more preferably 50mM:220mM:1.2mL.
[0030] In the present invention, in step 1), the temperature of the mixed reaction is 18-40°C, preferably 20-35°C, more preferably 25-30°C, and more preferably 28°C; the mixing reaction time is 8-12h, preferably 9-11h, and more preferably 10h; the drying temperature is 130-200°C, preferably 150-180°C, and more preferably 165°C; the drying time is 1-5h, preferably 2-4h, and more preferably 3h.
[0031] In the present invention, in step 2), the pyrolysis temperature is 600-800°C, preferably 650-750°C, and more preferably 700°C; the pyrolysis time is 2-4h, and more preferably 3h; the pyrolysis heating rate is 8-13°C / min, and more preferably 9-12°C / min, and more preferably 10°C / min.
[0032] In the present invention, in step 2), the drying temperature is 60-80°C, preferably 65-75°C, more preferably 70°C, and the drying time is 10-15h, preferably 13h;
[0033] The grinding particle size is through a 80-150 mesh sieve, preferably through a 100-130 mesh sieve, and more preferably through a 120 mesh sieve.
[0034] In the present invention, the washing is preferably performed using deionized water and ethanol to neutralize and then drying.
[0035] The invention provides a Co-loaded carbon-based catalyst prepared by the above preparation method.
[0036] The present invention also provides an application of a Co-loaded carbon-based catalyst in activating peroxymonosulfate to degrade organic components in biogas slurry. The Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate are sequentially mixed and reacted.
[0037] In the present invention, the usage ratio of the Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate is 0.2-1.0 g: 250-500 mL: 2.0-6.0 mM, preferably 0.5-0.8 g: 300-450 mM: 3.0-5.0 mM, further preferably 0.7 g: 350-400 mL: 4 mM, and more preferably 0.7 g: 370 mL: 4 mM.
[0038] In the present invention, the chemical oxygen demand concentration of the biogas slurry is 600-1000 mg / L, preferably 700-900 mg / L, and more preferably 800 mg / L. The pH value of the biogas slurry is 3.0-11.0, preferably 5.0-8.0, and more preferably 7.0.
[0039] In the present invention, the reaction temperature is 24-26° C., preferably 25° C., and the reaction time is 1-3 h, preferably 1.5-2.5 h, and more preferably 2 h.
[0040] In the present invention, ultraviolet full spectrum testing is used to measure the five-day biochemical oxygen demand (BOD5), COD value and conversion products of the biogas slurry after the Fenton-like reaction.
[0041] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0042] Example 1
[0043] 200 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 1 mL H2O2 were mixed and reacted at 25°C for 10 h, and then dried in a 160°C oven for 2 h to obtain the precursor Co@PDA; Co@PDA was placed in a tubular furnace for pyrolysis (pyrolysis temperature was 800°C, pyrolysis time was 4 h, and heating rate = 10°C / min), then washed with deionized water and ethanol until neutral, and dried in an oven at 60°C for 12 h, and ground through a 100-mesh sieve to obtain a Co-supported carbon-based catalyst, recorded as Co@CN-1:1;
[0044] At 25°C, 0.25 g of catalyst powder was added to 250 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 800 mg / L and a pH of 8.0. The pH value of the solution remained stable throughout the reaction. Subsequently, 4.0 mM permonosulfate was added to the mixed solution. After 2 hours of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0045] Example 2
[0046] 40 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 1 mL H2O2 were mixed and reacted at 35°C for 10 h, and then dried in a 160°C oven for 2 h to obtain the precursor Co@PDA. Co@PDA was placed in a tubular furnace for pyrolysis (pyrolysis temperature of 800°C, pyrolysis time of 2 h, heating rate = 8°C / min), then washed with deionized water and ethanol until neutral, and dried in a 60°C oven for 12 h. After grinding through a 100-mesh sieve, a Co-supported carbon-based catalyst was obtained, which was recorded as Co@CN-1:5.
[0047] At 24°C, 0.125 g of catalyst powder was added to 500 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 800 mg / L and a pH of 8.0. The pH value of the solution remained stable throughout the reaction. Subsequently, 3.0 mM permonosulfate was added to the mixed solution. After 1.5 h of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0048] Example 3
[0049] 20 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 1 mL H2O2 were mixed and reacted at 18°C for 10 h, and then dried in a 160°C oven for 2 h to obtain the precursor Co@PDA; Co@PDA was placed in a tubular furnace for pyrolysis (pyrolysis temperature of 800°C, pyrolysis time of 4 h, heating rate = 10°C / min), then washed with deionized water and ethanol until neutral, and dried in an oven at 60°C for 12 h, and ground through a 100-mesh sieve to obtain a Co-supported carbon-based catalyst, recorded as Co@CN-1:10;
[0050] At 26°C, 0.125 g of catalyst powder was added to 250 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 750 mg / L and a pH of 7.8. The pH of the solution remained stable during the entire reaction. Subsequently, 4.0 mM permonosulfate was added to the mixed solution. After 2 h of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0051] Example 4
[0052] 3.3 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 1 mL H2O2 were stirred at 25°C for 10 h, and then dried at 160°C for 2 h to obtain Co@PDA, which was then pyrolyzed in a tubular furnace (pyrolysis temperature of 800°C, pyrolysis time of 4 h, heating rate = 10°C / min), then washed with deionized water and ethanol until neutral, and dried in an oven at 60°C for 12 h. After grinding through a 100-mesh sieve, a Co-supported carbon-based catalyst was obtained, recorded as Co@CN-1:60;
[0053] At 24°C, 0.5 g of catalyst powder was added to 500 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 750 mg / L and a pH of 7.8. The pH value of the solution remained stable during the entire reaction. Subsequently, 3.0 mM permonosulfate was added to the mixed solution. After 1.5 h of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0054] Example 5
[0055] 200 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 1.5 mL H2O2 were stirred at 18°C for 10 h, and then dried at 200°C for 1 h to obtain Co@PDA, which was then pyrolyzed in a tubular furnace (pyrolysis temperature was 800°C, pyrolysis time was 2 h, and heating rate = 13°C / min), then washed with deionized water and ethanol until neutral, and dried in an oven at 80°C for 10 h, and ground through a 150-mesh sieve to obtain a Co-supported carbon-based catalyst;
[0056] At 26°C, 1 g of catalyst powder was added to 500 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 1000 mg / L and a pH of 3.0. The pH value of the solution remained stable throughout the reaction. Subsequently, 6.0 mM permonosulfate was added to the mixed solution. After 3 hours of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0057] Example 5
[0058] 100 mM cobalt chloride hexahydrate (CoCl2·6H2O), 200 mM dopamine and 0.8 mL H2O2 were stirred at 35°C for 8 h, and then dried at 130°C for 5 h to obtain Co@PDA, which was then pyrolyzed in a tubular furnace (pyrolysis temperature of 600°C, pyrolysis time of 4 h, heating rate = 8°C / min), then washed with deionized water and ethanol until neutral, and dried in an oven at 60°C for 15 h. After grinding through an 80-mesh sieve, a Co-supported carbon-based catalyst was obtained;
[0059] At 25°C, 0.2 g of catalyst powder was added to 250 mL of biogas slurry with a chemical oxygen demand (COD) concentration of 600 mg / L and a pH of 11.0. The pH value of the solution remained stable throughout the reaction. Subsequently, 2.0 mM permonosulfate was added to the mixed solution. After 3 hours of reaction, the catalyst was separated from the biogas slurry and the biogas slurry was measured.
[0060] It can be seen from the above embodiments that the present invention provides a Co-loaded carbon-based catalyst and a preparation method and application thereof. Figure 1The XRD patterns of the Co-loaded carbon-based catalysts obtained in Examples 1 to 4 show that the XRD patterns of Co@CN-1:5, Co@CN-1:10, and Co@CN-1:60 show a strong peak at 25°, and the peak shape is relatively wide, corresponding to the (002) diffraction of graphite carbon. Two characteristic diffraction peaks of cobalt appear at 44.2° and 47.5°, respectively, which indicates that the cobalt salt is successfully reduced to obtain elemental cobalt during the catalyst preparation process. The diffraction peak of the Co@CN-1:1 sample at 47.5° is the strongest, which is related to the higher Co loading of the sample. In addition, the Co@CN-1:1, Co@CN-1:5, and Co@CN-1:10 samples have obvious peaks at 51.3°, which are characteristic peaks of Co(OH)2.
[0061] Figure 2 The XPS graphs of the Co-supported carbon-based catalysts obtained in Examples 1 to 4 are as follows: Figure 2 As shown in the figure, the Co contents in Co@CN-1:1, Co@CN-1:5, Co@CN-1:10, and Co@CN-1:60 are 4.88%, 3.22%, 0.91%, and 0.74%, respectively. The higher the Co content of the catalyst, the higher the intensity of the Co 2p characteristic peak. In addition, the N contents in Co@CN-1:1, Co@CN-1:5, Co@CN-1:10, and Co@CN-1:60 are 2.19%, 2.65%, 2.28%, and 4.06%, respectively. Among them, the N content of Co@CN-1:60 is higher, which may be related to the high content of dopamine precursors.
[0062] Figure 3 The figure is a schematic diagram of the improvement ratio of biodegradability of biogas slurry by Co-loaded carbon-based catalyst obtained in Examples 1 to 4. It can be seen from the figure that when the mixing ratio of Co to PDA is 1:1, the biodegradability of biogas slurry decreases. As the Co content decreases, the biodegradability of biogas slurry increases to 0.13, with an increase ratio of 19.0%. When the ratio of Co to PDA is 1:10, the B / C of biogas slurry reaches 0.18 after 1.5 hours of reaction, and the biodegradability improvement ratio is 37.4%.
[0063] Figure 4 The UV spectra of biogas slurry after PMS treatment with Co-supported carbon-based catalyst activation obtained in Examples 1 to 4 are shown. The intensity and position of the UV spectrum absorption peak are related to the type and content of organic matter in the water sample, usually related to unsaturated compounds containing C=C and C=O and polycyclic aromatic compounds. When the wavelength is greater than 400nm, the absorbance of the untreated biogas slurry and each sample after oxidation treatment is relatively small, and there is no obvious absorbance peak. Figure 4As shown in the figure, the raw water has obvious characteristic peaks at 250-280nm. This is because there are a large number of humic acid, lignin sulfonic acid and its derivatives in the untreated biogas slurry. These substances are prone to π-π electron transitions, resulting in an absorption peak at 280nm. After the PMS oxidation treatment was activated by four catalysts, the intensity of the characteristic peak at 250-280nm in the sample weakened, indicating that humic acid and lignin sulfonic acid were effectively degraded in the four systems. In addition, after Fenton-like oxidation, a low-intensity absorption platform appeared at 220-250nm, which may be related to the presence of conjugated double-bond organic matter in the oxidation product.
[0064] In summary, the present invention provides a precise strategy for the regulation of active sites and oxidizing species and the controllable conversion of difficult-to-biodegrade components. The present invention uses dopamine as a raw material, supplemented by a series of structural control methods, and controls the parameters of the preparation process to change the surface properties and structure of the carbon-based catalyst, control the active sites of the catalyst, and construct an efficient Fenton-like system to change the persulfate activation path and the types of active species produced, and control the conversion path of difficult-to-biodegrade components of the biogas slurry. The lignin macromolecular long-chain organic matter in the biogas slurry is controllably converted into small molecular organic matter, thereby improving the biodegradability of the biogas slurry and promoting its clean reuse.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Co-supported carbon-based catalyst, characterized in that: The following steps are involved: 1) Cobalt chloride hexahydrate, dopamine and H2O2 are mixed and reacted, and then dried to obtain Co@PDA; 2) The Co@PDA obtained in step 1) is pyrolyzed, washed, dried and ground in sequence to obtain a Co-supported carbon-based catalyst.
2. The method for preparing a Co-supported carbon-based catalyst according to claim 1, characterized in that: In step 1), the usage ratio of cobalt chloride hexahydrate, dopamine and H2O2 is 3-200 mM: 180-250 mM: 0.8-1.5 mL.
3. The method for preparing a Co-supported carbon-based catalyst according to claim 1 or 2, characterized in that: In step 1), the temperature of the mixing reaction is 18-40° C., and the mixing reaction time is 8-12 hours; the temperature of the drying is 130-200° C., and the drying time is 1-5 hours.
4. The method for preparing a Co-supported carbon-based catalyst according to claim 3, characterized in that: In step 2), the pyrolysis temperature is 600-800° C., the pyrolysis time is 2-4 hours, and the pyrolysis heating rate is 8-13° C. / min.
5. A method for preparing a Co-supported carbon-based catalyst according to claim 1, 2 or 4, characterized in that: In step 2), the drying temperature is 60-80°C and the drying time is 10-15h; The grinding particle size is passed through a 80-150 mesh sieve.
6. The Co-supported carbon-based catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the Co-supported carbon-based catalyst according to claim 6 in activating peroxymonosulfate to degrade organic components in biogas slurry, characterized in that: The Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate are sequentially mixed and reacted.
8. The use of a Co-loaded carbon-based catalyst in improving biodegradability of biogas slurry according to claim 7, characterized in that: The usage ratio of the Co-loaded carbon-based catalyst, biogas slurry and peroxymonosulfate is 0.2-1.0 g: 250-500 mL: 2.0-6.0 mM.
9. Use of a Co-loaded carbon-based catalyst in improving biodegradability of biogas slurry according to claim 7 or 8, characterized in that: The chemical oxygen demand concentration of the biogas slurry is 600-1000 mg / L, and the pH value of the biogas slurry is 3.0-11.
0.
10. The use of a Co-loaded carbon-based catalyst in improving biodegradability of biogas slurry according to claim 7, characterized in that: The reaction temperature is 24-26° C., and the reaction time is 1-3 hours.
Citation Information
Patent Citations
Oil sludge carbon supported metal catalyst, and preparation method and application thereof
CN110548515A
Carbonized polydopamine coated cobalt nanoparticle material and preparation and application methods thereof
CN114100666A
Tissue-catalyzed growth of polymers as epithelial therapy
CN114929198A
Kitchen waste slurry enhanced treatment process
CN115340260A
Surface treating agent used before coating of galvanized sheet
CN116180062A